Clinical Features of Spontaneous Partial Healing During Mycobacterium ulcerans Infection. (25th February 2016) - Marion, Estelle; Chauty, Annick; Kempf, Marie; Le Corre, Yannick; Delneste, Yves; Croue, Anne; Marsollier, Laurent; ,; Vincent, Quentin B.; Abel, Laurent; Johnson, Christian; Alcaïs, Alexandre; et al.
Abstract: Background. Buruli ulcer, caused by Mycobacterium ulcerans, is a necrotizing skin disease leading to extensive cutaneous and subcutaneous destruction and functional limitations. Spontaneous healing in the absence of medical treatment occurs in rare cases, but this has not been well described in the literature. Methods. In a retrospective case study in an area of Benin where this disease is highly endemic, we selected 26 Buruli ulcer patients presenting features of spontaneous healing from a cohort of 545 Buruli ulcer patients treated between 2010 and 2013. Results. The 26 patients studied had a median age of 13.5 years and were predominantly male (1.4:1). Three groups of patients were defined on the basis of their spontaneous healing characteristics. The first group (12 patients) consisted of patients with an ulcer of more than 1 year′s duration showing signs of healing. The second (13 patients) group contained patients with an active Buruli ulcer lesion some distance away from a first lesion that had healed spontaneously. Finally, the third group contained a single patient displaying complete healing of lesions from a nodule, without treatment and with no relapse. Conclusions. We defined several features of spontaneous healing in Buruli ulcer patients and highlighted the difficulties associated with diagnosis and medical management. Delays in consultation contributed to the high proportion of patients with permanent sequelae and a risk of squamous cell carcinoma. Early detection and antibiotic treatment are the best ways to reduce impairments.